Current clinical practice and challenges in the management of secondary immunodeficiency in hematological malignancies. (24th March 2019) - Na, Il‐Kang; Buckland, Matthew; Agostini, Carlo; Edgar, John David M.; Friman, Vanda; Michallet, Mauricette; Sánchez‐Ramón, Silvia; Scheibenbogen, Carmen; Quinti, Isabella
Abstract: Objective: Despite long‐standing safe and effective use of immunoglobulin replacement therapy (IgRT) in primary immunodeficiency, clinical data on IgRT in patients with secondary immunodeficiency (SID) due to B‐cell lymphoproliferative diseases are limited. Here, we examine the correlation between approved IgRT indications, treatment recommendations, and clinical practice in SID. Methods: An international online survey of 230 physicians responsible for the diagnosis of SID and the prescription of IgRT in patients with hematological malignancies was conducted. Results: Serum immunoglobulin was measured in 83% of patients with multiple myeloma, 76% with chronic lymphocytic leukemia, and 69% with non‐Hodgkin lymphoma. Most physicians (85%) prescribed IgRT after ≥2 severe infections. In Italy, Germany, Spain, and the United States, immunoglobulin use was above average in patients with hypogammaglobulinemia, while in the UK considerably fewer patients received IgRT. The use of subcutaneous immunoglobulin was highest in France (34%) and lowest in Spain (19%). Immunologists measured specific antibody responses, performed test immunization, implemented IgRT, and used subcutaneous immunoglobulin more frequently than physicians overall. Conclusions: The management of SID in hematological malignancies varied regionally. Clinical practice did not reflect treatment guidelines, highlighting the need for robust clinical studies on IgRT in this population and harmonization between countries and disciplines.